Basel II compliant mapping of operational risks - Schäl, Ingo; Stummer, Wolfgang (Journal of Operational Risk, 2007)
We discuss some issues concerning the unambiguous categorization and mapping of operational risk, in the sphere of the Basel II Accord. Special emphasis is put on the role of appropriate "semi-coarse template categorizations". Such a template consisting of 100 categories is presented in detail and principally interlinked with current operational risk evaluation methods.